AMOXICILLIN/CLAVULANAT EFFICIENCY FOR TREATMENT OF CHILDREN WITH COMMUNITY-ACQUIRED PNEUMONIA - O.I. Pikuza; A.M. Zakirova; E.A. Samorodnova; Kh.M. Vakhitov; T.B. Moroz (Педиатрическая фармакология)
Research goal — comparative evaluation of efficiency of amoxicillin/clavulanat versus unprotected penicillins and first generation cephalosporins for treatment of children with acute community acquired pneumonia. 62 children with acute pneumonia took part in the research. The main group was comprised of 47 children aged 3–17 who received amoxicillin/clavulanat, comparison group — of 16 children who received unprotected penicillins or first generation cephalosporin. Treatment efficiency was evaluated by the main clinical symptoms changes dynamics. Amoxicillin/clavulanat clinical efficiency amounted to 87,23%. Compared to comparison group, treatment with amoxicillin /clavulanat helped to speed up reduction of inflammatory processes in lungs, prevent the need for refresher courses of treatment with antimicrobials, reduce the time of stay in hospital and total amount of received medication. Research results prove the advisability of more extensive amoxicillin/clavulanat use for treatment of patients with acute community acquired pneumonia both in hospital environment and in outpatient situations.Key words: antimicrobials, amoxicillin/clavulanat, treatment, pneumonia, children.